Susceptibility of Shallot cv Tajuk Cultivated in Bantul and Kulon Progo Against Fusarium Disease - Siti Nur Aisyah; Qorina Vivianty Fajrin; Intania Puspa Dewi; Taufiq Hidayat; Agung Astuti; Jennifer Ann Harikrishna (Agrotechnology Research Journal, 2025)
Shallot cv. Tajuk is one of the most preferred shallot varieties to be cultivated, especially by farmers living in lowland areas with low water availability issues, such as Bantul and Kulon Progo. However, to date, the information about the resistance of this variety to Fusarium disease is poorly studied. Therefore, this study aims to investigate the prevalence of Fusarium disease in shallot cv. Tajuk is cultivated in Bantul and Kulon Progo. A survey of Fusarium disease occurrence was conducted in 8 shallot fields from 3 districts in Bantul (Imogiri, Sanden, and Kretek) and six shallot fields representing two districts of Kulon Progo (Lendah and Sentolo). Disease observation in Bantul was carried out during the dry season from June to August 2023, while the survey in Kulon Progo was performed during the rainy season from January to February 2024. The cropping system applied in each selected shallot field was also collected through the landowner interviews. Data obtained from disease monitoring were statistically analyzed using one-way analysis of variance (ANOVA), and significance among locations was subsequently analyzed using Duncan’s New Multiple Range Test with a p<0.05. Findings of this study revealed that the susceptibility of shallot cv. Tajuk to Fusarium disease varied between Bantul and Kulon Progo. Shallot var. Tajuk conferred higher resistance against Fusarium disease when it was cultivated in Kulon Progo. Results of this study also confirmed that different farming practices applied in each location appear to have a minor impact on the severity of this disease in the shallot cv. Tajuk